Why do Refugees have to Leave their Sweet Home “Unless home is the Mouth of a Shark”? An Analysis of Warsan Shire’s Poem Home - Gunes, Ali (Journal of History Culture and Art Research, 2019)
This paper analyses in Warsan Shire’s poem Home why refugees have to leave their home. In so doing, it first explores the root causes behind particularly the displacement of Somalians, which becomes an inspiration for the poem and also argues that these causes may actually be similar ones which could be seen one way or another behind any act of the displacement anywhere across the world. Secondly, the paper responds to the criticisms which accuse refugees of leaving at once their home when they face any difficulties in life. In this sense, the poem becomes the voice of “refugees” and tells the world that “refugees” will not take all the risks in very dangerous and difficult journeys without any reasonable causes. As the paper discusses, what is also equally important is that “refugees,” though exposed to very hard conditions of living during the journey and in the host country, are also labelled as “Other,” which immediately brings about a negative condition, in which they are humiliated, discriminated and categorised as “us” and “them, making it difficult for refugees to integrate and eventually belong to the indigenous society. Finally, the paper debates that it is not the guilt of refugees who leave their home but the ones who create intolerable causes for their displacement from their home. The paper suggests that we are all responsible - United Nations, politicians, world leaders, writers, intellectuals, and academics and so on all over the world - not only for revealing the root causes behind the displacement of people from their home but also for annihilating them all together for a humanely world and living.